Antibacterial activity of combined extracts of red ginger (Zingiber officinale var. Rubrum) and betel leaf (Piper betle L.) against Staphylococcus aureus and Escherichia coli - Oktariani Pramiastuti; Joharoh (Medical Laboratory Analysis and Sciences Journal, 2020)
The use of traditional medicine can be an alternative treatment with increasing antibiotic resistance. Red ginger (Zingiber officinale var. Rubrum) and betel leaf (Piper betel L.) are plants that can be used as an antibacterial. This study aimed to determine the antibacterial activity of combined extracts of red ginger and betel leaf. This experiment was carried out by making extracts of red ginger and betel leaf with maceration and tested the antibacterial activity. The antibacterial activity test used the paper disc diffusion method. The study was conducted with five different concentrations of extract 20%, 40%, 60%, 80%, and 100%. The results showed that the combination of red ginger and betel leaf extract at a concentration of 80% had the highest inhibitory area against Staphylococcus aureus (10.6 mm) and Escherichia coli (7.5 mm). The data obtained were statistically tested using One Way Anova with a significance level of > 0.05. The results of One Way ANOVA analysis of the combination of red ginger and betel leaf extracts on Staphylococcus aureus had a significant value of 0.083, while those extracts on Escherichia coli had a significant value of 0.690. It can be concluded that the combination of red ginger and betel leaf extract at a concentration of 80% had a strong inhibitory level against Staphylococcus aureus and a moderate inhibitory level against Escherichia coli.